Aspergillus epiglottitis in a non-immunocompromised patient. (25th February 2011) - Durell, J; Taha, R; Pipi, G; Oko, M
Abstract : The authors present a case that highlights an atypical example of a fungal epiglottis in an otherwise well adult patient with no medical history of fungal infection or an immunocompromised state. As current medical literature presents this fungus as only manifesting in the immunocompromised, the authors suggest, by this case report, that fungal pathogens be considered as a potential cause of epiglottitis in non-immunocompromised patients.